English Language Learning for Culinary Arts Students: Obstacles and Expectations - Pratita Pawestri; Fajria, Astry (Universitas Ahmad Dahlan, 2024)
Mastering English learning as a culinary arts student is important. Culinary arts students need to be able to understand English to help them interact with customers, understand recipes and instructions in English, and also collaborate with culinary professionals from different countries. However, in practice, students often experience obstacles in learning which also leads to students' expectations of English language learning. Therefore, the study aims to find out culinary arts students' obstacles and expectations of English learning. The research subjects were culinary arts students of SMK Muhammadiyah 4 Yogyakarta, consisting of 5 female and 5 male students. The research subjects were randomly selected by the English teacher. In this case, the research method used is descriptive qualitative. The data was obtained by using a semi-structured interview method in a face-to-face. The instrument used in this research is an interview guideline consisting of fifteen questions related to students’ obstacles and expectations. Data from the interview were analyzed in a qualitative data analysis stages. After conducting the research process, it was found that culinary arts students' obstacles of English learning were: ontogenic obstacles shown by students' disinterest in learning English; didactical shown by students' dissatisfaction with the way teachers teach; and epistemological obstacles shown by students' lack of understanding in learning English. Students’ expectations of English learning also found that students expect a variation of learning, learn outside the classroom, learn English to be adjusted to students' abilities, and prefer learning with more emphasis on speaking skills.